Foreign Direct Investments into Eastern Africa Region: The Governance Paradox - Bosire, Eric M. (International Journal of Economics and Financial Issues, 2019)
The role governance structures play in economic growth and development cannot be over emphasised. According to the World Bank, indicators that define governance include; Government effectiveness, control of corruption, political stability and absence of violence/terrorism, regulatory quality, rule of law, and voice and accountability. Regrettably, there has been limited attention to how governance indicators influence the flow of foreign direct investments. Therefore, this paper presents results from an extensive study on governance and foreign direct investments into 12 eastern Africa countries for the periods 2002 through 2016. By the use of generalized least squares on panel data, the study established that governance indicators do not have any significant relationship with the flow of foreign direct investments into the eastern Africa region, but when this relationship is controlled by availability of natural resources, exports, imports and labour force, the relationship turn significant. It is therefore, obligatory for countries to ensure a stable political environment which promotes security for both life and property. Additionally, institutions that promote public service delivery should be free from political patronage, align policy making and implementation to the development of the private sector and preventing corruption of all forms. Keywords: Foreign direct investments, Government effectiveness, Control of Corruption, Political stability and absence of violence/terrorism, Regulatory quality, JEL Classifications: E22, F21, G34, C55 DOI: https://doi.org/10.32479/ijefi.7407